2012
DOI: 10.1063/1.4733675
|View full text |Cite|
|
Sign up to set email alerts
|

How to recover Marcus theory with fewest switches surface hopping: Add just a touch of decoherence

Abstract: We present a slightly improved version of our augmented fewest switches surface hopping (A-FSSH) algorithm and apply it to the calculation of transition rates between diabatic electronic states within the spin-boson model. We compare A-FSSH rates with (i) Marcus rates from the golden rule, (ii) Tully-style FSSH rates, and (iii) FSSH rates using a simple, intuitive decoherence criterion. We show that unlike FSSH, A-FSSH recovers the correct scaling with diabatic coupling (quadratic in V) as well as the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
189
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(197 citation statements)
references
References 50 publications
7
189
1
Order By: Relevance
“…13,14,18 One method uses exclusively the electronic wavefunction of each trajectory. The other uses only the active surface of each trajectory.…”
Section: Theory: Basis Set Conversionmentioning
confidence: 99%
“…13,14,18 One method uses exclusively the electronic wavefunction of each trajectory. The other uses only the active surface of each trajectory.…”
Section: Theory: Basis Set Conversionmentioning
confidence: 99%
“…Subotnik and Shenvi 21 proposed a prescription for decoherence correction to FSSH dynamics. Landry et al 22 showed that implementing a decoherence correction in the FSSH algorithm leads to the recovery of Marcus theory in the calculation of transition rates between adiabatic electronic states within the spin-boson model. As will be discussed later, in the present work trajectories quickly leave the interaction region and almost never return to it.…”
Section: Introductionmentioning
confidence: 99%
“…(6) corresponds to electronic dephasing is also the main reason for why predictions based on methods like fewest-switches surfacehopping, [20][21][22]59,60 Ehrenfest dynamics, 20 and ring-polymer molecular dynamics 19 …”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…(A. 22). To this end, we start out by noting that the Jacobian of changing integration variables from y 1 , .…”
Section: Appendix B Proof Of Identity Equation A22mentioning
confidence: 99%